THE EFFECT OF ROLE PLAYING STRATEGY ASSISTED BY PAPER PUPPETS AS MEDIA TO THE STUDENTS’ SPEAKING COMPETENCY - Putu Indra Yani; I N Jampel; I N Jayanta (Journal of Psychology and Instruction, 2018)
The purpose of this study is to determine the speaking skill differences regarding to Bahasa as the subject between students who were taught by using puppet show as media of role-play supporting model and students who were not taught by using puppet show at second semester of fifth grade elementary school on Cluster III of Banjar District, Buleleng Regency in academic year 2017/2018. The population of this research is the 114 fifth grade students on Cluster III Banjar District, Buleleng Regency in academic year 2017/2018 as well. Meanwhile, the samples of the research are 17 fifth grade students from SD Negeri 2 Dencarik and 15 fifth grade students from SD Negeri 3 Dencarik. Assessment of speech is used as the instrument of data collection. Then, the collected data is analyzed by using descriptive and inferential statistical analysis (t-test). Tcal = 6,93 > ttab = 1,69 is obtained based on the results of analysis which means that there is significant difference between students who were taught by using puppet show as media of role-play supporting model and students who were not taught by using puppet show for Bahasa as learning subject for second semester of fifth grade elementary school on Cluster III of Banjar District, Buleleng Regency in academic year 2017/2018. This researcher suggests that it can be used as a guide in further research about puppest show as media of role-play supporting model in Bahasa or any other subject as field of study.